ON RENTS - V. V. Mnishko (Научный вестник МГТУ ГА, 2016)
The article considers the problem of determining lease rates for land plots granted for aerodromes, heliports and landing-grounds, airports, objects, EU EO VD, analyzes the situation with the lease of lands for road and rail transport and a comparison with air travel is given. In addition, the problem of transfer of land from the categories of settlements into the category of transport is examined, it is concluded that rents for civil aviation are discriminatory and do not comply with the recommendations of the International organization of civil aviation (ICAO) according to their size. Appropriate recommendations are given.